Can Nanofluidic Chemical Release Enable Fast, High Resolution Neurotransmitter-Based Neurostimulation? - Jones, Peter D.; Stelzle, Martin (Frontiers in Neuroscience, 2016)
Artificial chemical stimulation could provide improvements over electrical neurostimulation. Physiological neurotransmission between neurons relies on the nanoscale release and propagation of specific chemical signals to spatially-localized receptors. Current knowledge of nanoscale fluid dynamics and nanofluidic technology allows us to envision artificial mechanisms to achieve fast, high resolution neurotransmitter release. Substantial technological development is required to reach this goal. Nanofluidic technology — rather than microfluidic — will be necessary; this should come as no surprise given the nanofluidic nature of neurotransmission. This perspective reviews the state of the art of high resolution electrical neuroprostheses and their anticipated limitations. Chemical release rates from nanopores are compared to rates achieved at synapses and with iontophoresis. A review of microfluidic technology justifies the analysis that microfluidic control of chemical release would be insufficient. Novel nanofluidic mechanisms are discussed, and we propose that hydrophobic gating may allow control of chemical release suitable for mimicking neurotransmission. The limited understanding of hydrophobic gating in artificial nanopores and the challenges of fabrication and large-scale integration of nanofluidic components are emphasized. Development of suitable nanofluidic technology will require dedicated, long-term efforts over many years.